The ocs element: a 16 base pair palindrome essential for activity of the octopine synthase enhancer - Ellis, J. G. (1987)
A 176 bp DNA sequence lying upstream of the octopine synthase (ocs) promoter, previously shown to have enhancer-like properties in transgenic tobacco [Ellis et al. (1987) EMBO J., 6, 11-16], functions as an enhancer in protoplasts of Zea mays (a monocot plant) and Nicotiana plumbaginifolia (a dicotplant). We have characterized this element by transient expression assays using a linked alcohol dehydrogenase (Adh1) promoter from Z. mays and the chloramphenicol acetyltransferase coding sequences. The ocs sequence functions in both orientations but its enhancing activity is dependent upon its distance from the Adh1 promoter. Transient expression assays using deletion mutants and synthetic oligonucleotides show that a 16 bp palindrome ACGTAAGCGCTTACGT, contained within the 176 bp fragment, is essential and sufficient for enhancing activity in transient expression assays.